Negotiating Relationally: The Dynamics of the Relational Self in Negotiations - Gelfand, Michele J.; Major, Virginia Smith; Raver, Jana L.; Nishii, Lisa H.; O'Brien, Karen (Academy of Management Review, 2006)
In this article we advance a distinctly relational view of negotiation. We delineate the conditions through which relational self-construals (RSC) become accessible in negotiations and the conditions that inhibit their use, and we illustrate mechanisms through which RSC affects negotiation processes and outcomes. We introduce four relational dynamics–arelational trading, relational satisficing, relational distancing, and relational integrating–and discuss their consequences for the accumulation of economic and relational capital in negotiation.